Targeting LRP8 inhibits breast cancer stem cells in triple-negative breast cancer. (1st December 2018) - Lin, Chang-Ching; Lo, Miao-Chia; Moody, Rebecca; Jiang, Hui; Harouaka, Ramdane; Stevers, Nicholas; Tinsley, Samantha; Gasparyan, Mari; Wicha, Max; Sun, Duxin
Abstract: Triple-negative breast cancer (TNBC) is the most difficult subtype of breast cancer to treat due to a paucity of effective targeted therapies. Many studies have reported that breast cancer stem cells (BCSCs) are enriched in TNBC and are responsible for chemoresistance and metastasis. In this study, we identify LRP8 as a novel positive regulator of BCSCs in TNBC. LRP8 is highly expressed in TNBC compared to other breast cancer subtypes and its genomic locus is amplified in 24% of TNBC tumors. Knockdown of LRP8 in TNBC cell lines inhibits Wnt/β-catenin signaling, decreases BCSCs, and suppresses tumorigenic potential in xenograft models. LRP8 knockdown also induces a more differentiated, luminal-epithelial phenotype and thus sensitizes the TNBC cells to chemotherapy. Together, our study highlights LRP8 as a novel therapeutic target for TNBC as inhibition of LRP8 can attenuate Wnt/β-catenin signaling to suppress BCSCs. Highlights: Higher expression of LRP8 is associated with TNBC and poor prognosis. Knockdown of LRP8 suppresses BCSCs in TNBC via inhibiting Wnt/β-catenin signaling. Targeting LRP8 shifts TNBC cells to a more differentiated, epithelial cell state.